Algunos problemas definitorios y terminológicos en el àmbito de estudios fraseológicos españoles - Szałek, Jerzy (Studia Romanica Posnaniensia, 2003)
The article discusses some of the essential theoretical and terminological issues in contemporary studies of Spanish phraseology and phraseography. The controversial definitional problems of Modern Spanish phraseology have been presented on the basis of concepts of indiscreet and cognitive interpretation. The examples provided come from contrastive Spanish-Polish phraseology.